Guilt-Tripping: On the Relation between Ethical Decisions, Climate Change and the Built Environment - Prieto de la Fuente, Paulina (2020)
The curiosity of how the built environment, implicitly and explicitly, affects how citizens and users make choices in their everyday life related to climate change is on the rise. If there is a nicely designed bike lane, the choice to bike to work is much more easily taken than if the only option is a densely trafficked road. But which responsibility does the built environment have for citizens to be as climate neutral as possible and, in extension, who should it burden? Is it the individual user, the designer, the planner, the policymaker or global politics? Media is playing an important and complicated role here; it works both as a source of information and as a trigger, instigating both feelings of guilt, fear, and shame in order to set change in motion. In this article, I will discuss everyday climate-related decision-making fuelled by shame and guilt, drawing on Judith Butler’s writings on ethical obligations and narrating it with findings from a mapping study of daily transportation routes that I conducted in a middle-class suburb outside of Lund, in Sweden. There appears to be a dissonance between the relatively high knowledge about one’s responsibility concerning climate change and the limited space to manoeuvre in everyday life. Even though shame and guilt may be driving forces to make decisions, the possibility to imagine and to change needs to be expanded.